2014
DOI: 10.1097/pas.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Leiomyomas With Bizarre Nuclei

Abstract: Leiomyoma with bizarre nuclei (LM-BN) is an uncommon tumor with histologic features (mononucleated or multinucleated bizarre cells that may have a diffuse distribution, prominent nucleoli, and karyorrhectic nuclei that may mimic atypical mitoses) that often causes confusion with leiomyosarcoma. Fifty-nine LM-BNs were collected from our consultation files over the years 2000 to 2011. Features recorded included patient age, therapy, tumor size, border, gross appearance, density and distribution of BN, mitotic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Past studies have shown variable Ki-67 percentages among ALM cases, ranging from 0 to 30% (3, 4). Our study showed similar variability, although most cases had low proliferation rates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Past studies have shown variable Ki-67 percentages among ALM cases, ranging from 0 to 30% (3, 4). Our study showed similar variability, although most cases had low proliferation rates.…”
Section: Resultsmentioning
confidence: 99%
“…Croce et al (4) provided a comprehensive evaluation of histologic features in their study of 59 ALM cases where they analyzed features including cellularity, density of nuclear atypia, mitotic count, presence of prominent nucleoli, karyorrhectic nuclei, pseudonuclear inclusions, rhabdoid-like cells, vascular changes, eosinophilic hyaline globules, and ischemic necrosis. In this study, they found that 18 cases showed diffuse atypia, 26 showed multifocal atypia and 15 showed focal atypia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations